Media effects: Do terrorist organizations launch foreign attacks in response to levels of press freedom or press attention?. (September 2016) - Asal, Victor; Hoffman, Aaron M.
Terrorists are supposed to be influenced by opportunities for news coverage, but does this mean that groups initiate foreign attacks in response to the absence of press freedom in their country or inattention to that state by foreign media organizations? Using Asal and Rethmeyer's BAAD1 data on terrorist organizations, we find that increasing levels of attention by the international press reduce the odds of groups launching cross-border attacks. The propensity of groups to launch foreign attacks appears unrelated to press freedom. These results suggest that the protections that states provide for the press motivate foreign terrorism less than the way the media determines newsworthiness.